The Fifty-fifty Man - Satarupa Sahoo (Jurnal Langua, 2022)
Indo-Canadian Diasporic literatures deal with the displacement of identities andthe cultural assimilation that occurs over generation and with re-discovering the‘hyphenated-identities’ that forms a major part of a diaspora. The constantconflict between ‘homeland’ and the ‘host-land’ creates a feeling ofdisplacement that becomes a central theme for diasporic literatures. Indo-Canadian diasporic people bond over their shared nostalgia of the homeland –they experience a sort of parallel existence with one foot in the homeland andthe other in the host-land. Through the two prominent novels of Indo-Canadiandiaspora – Anita Rau Badami’s Can You Hear The Nightbird Call? AndRohinton Mistry’s A Fine Balance we understand the diasporic identity andwhat it entails. We will study how the characters in both the novels are alleffected by the socio-political and economic conditions of India during the 1975Emergency and how it alters each character. Badami’s novel moves between theSikhs living in India and Sikhs living in Canada and the plight of them, whileMistry deals with Hindu - Muslim conflicts. This paper focuses on how readingthese Canadian literatures during a worldwide Covid-19 pandemic changesone’s understanding of diasporic literature, cultures and diasporic identities.In a covid-19 pandemicsituation when many Indians living in Canada are horrified about the conditionsin their homeland, their helplessness for not being able to visit, relying onvirtual world/online modes of communication to keep themselves up to date onthe conditions in their homeland. Reading Canadian literatures with historicalcontexts of crisis situations, mass deaths, economic and sociological downfall,political crisis etc., at a time when we ourselves are undergoing or rathersurviving through a worldwide pandemic with countless deaths, economicdownfall etc., shapes or alters the approach towards diasporic literatures givingus a better understanding of Canadian literatures.